Why declare independence? Observing, believing, and performing the ritual. Issue 2 (22nd April 2021) - Knotter, Lucas
Abstract: Declarations of independence continue to be commonplace in international affairs, yet their efficacy as means towards statehood remains disputed in traditional international legal and political thinking and conduct. Consequently, recent scholarship on state recognition and emerging statehood suggests that the international persistence of such declarations should be understood in the context of broader international processes, narratives, and assemblages of state creation. Such suggestions, however, risk reifying declarations' effectiveness more in relation to international structure(s) than to independence movement's own agency. This article, therefore, calls for a reframing of declarations of independence as a ritual in international relations. It argues that participating in the international ritual of independence declaration forms an attempt to 'fuse' the movement's political practice with international recognition, serves to express an internal belief in 'redemption' through the 'ascension' into the 'celestial' existence of recognised statehood, and offers an opportunity to internally bolster political community through political performance. Ritual theory, thus, uncovers how the global persistence of independence declarations cannot be explained merely through discrete oppositions of non-recognition versus recognition, belief versus reality, and/or non-state versus state community, and instead opens up new space for understanding the contradictions characterising the international political (in)significance and persistence of statehood declarations.